CEO pay, firm performance, and corporate governance in India's listed firms. (30th November 2009) - Jaiswall, Manju; Firth, Michael
In this study we examine the determinants of CEO compensation in large listed Indian companies. There is a positive relation between pay and a firm's performance. We find that remuneration committees are related to higher CEO compensation and there is no association between remuneration committees and pay-performance sensitivities. Thus, remuneration committees do not act in the way predicted by governance guidelines. CEOs in family firms are paid more. This suggests that CEOs use their power as a member of the controlling family to obtain higher compensation. The minority shareholders are therefore disadvantaged. CEOs in risky firms are paid less.